1998
DOI: 10.1093/oxfordjournals.pubmed.a024744
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index: a comparison between self-reported and measured height and weight

Abstract: Self-reported heights and weights are unreliable and if used for monitoring health targets should be treated with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(85 citation statements)
references
References 4 publications
5
77
2
1
Order By: Relevance
“…However, several US and European studies [10][11][12][13][14][15][16] have shown that errors in self-reported weight and height underestimate the prevalence of overweight and obesity, and that measured obesity has a strong association with bias in selfreported BMI. Similar results are reported in this populationbased study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several US and European studies [10][11][12][13][14][15][16] have shown that errors in self-reported weight and height underestimate the prevalence of overweight and obesity, and that measured obesity has a strong association with bias in selfreported BMI. Similar results are reported in this populationbased study.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Several studies have shown high correlation between selfreported and measured BMI, [8][9][10] but systematic errors in selfreported values may affect the distribution of BMI, and consequently the prevalence of obesity. [10][11][12][13][14][15] The aims of our study were to evaluate the effect of misclassification of BMI in the association between obesity and asthma by gender.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found systematic mis-reporting of weight and height in males and females of all adult ages, with those who are more overweight and shorter having a greater tendency to under Childhood intelligence, educational attainment and adult BMI DA Lawlor et al report their weight and over report their height. 27,28 This mis-reporting would need to have been more marked in those with higher intelligence test scores in childhood and greater educational attainment for it to explain the inverse associations that we have found. The similarity in our findings to those from two other prospective studies 9,10 with less loss to follow-up and that used actual measurements of weight and height to calculate BMI suggest that our results have not been markedly biased by loss to follow-up and use of self-report to assess height and weight.…”
Section: Study Limitationsmentioning
confidence: 91%
“…However, these findings are not always consistent (Hill & Roberts, 1998) and therefore the self-report of such measures may introduce bias, specifically if participants consistently over-or underestimated their height and weight resulting in skewed data. It is important to note that many of the participants availed themselves of the scale and height chart provided on the day of the survey, and the research team helped them to measure and then record their numbers.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%